2006
DOI: 10.1128/aac.50.3.1089-1091.2006
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus Efflux msr (A) Gene Characterized in Streptococcus , Enterococcus , Corynebacterium , and Pseudomonas Isolates

Abstract: The staphylococcal msr(A) gene, coding for a macrolide efflux protein, was identified in three new grampositive genera and one gram-negative genus. These msr(A) genes shared 99 to 100% identity with each other and the staphylococcal gene. This study demonstrates that the msr(A) gene has a wider host range than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…Regarding Enterobacteriaceae, the msr(A) gene has only been reported in an isolate of Enterobacter spp., in which no other of the macrolide-resistance mechanisms sought was found (Ojo et al, 2006). This isolate presented high levels of erythromycin resistance, despite some reports indicating a loss of MsrA activity when cloned in E. coli (Matsuoka et al, 1999).…”
Section: Transferable Efflux Pumpsmentioning
confidence: 91%
“…Regarding Enterobacteriaceae, the msr(A) gene has only been reported in an isolate of Enterobacter spp., in which no other of the macrolide-resistance mechanisms sought was found (Ojo et al, 2006). This isolate presented high levels of erythromycin resistance, despite some reports indicating a loss of MsrA activity when cloned in E. coli (Matsuoka et al, 1999).…”
Section: Transferable Efflux Pumpsmentioning
confidence: 91%
“…73 A macrolide-specific ABC-type pump, macAB , has been identified in E. coli , 74 while the Msr family of macrolide pumps is known to have spread from Staphylococcus to other genera such as Streptococcus and Pseudomonas. 75 Among Gram-negative bacteria, the RND family is a major class of multidrug efflux pumps, which partially account for the persistence of these pathogens in clinical settings. 76,77 Recent studies have identified amino acid residues specifically responsible for macrolide resistance via the RND transporter complex AcrAB-TolC in E. coli .…”
Section: Macrolides and Ketolides–from Fermentation To Synthesismentioning
confidence: 99%
“…High homology ( 1 98% identity) variants of the msr(A) determinant have been identified in both S. aureus ( msr (SA) and msr (SA)) and S. xylosus ( msr (B)) [Roberts et al, 1999]. In addition to these staphylococcal species, msr (A) determinants have also been identified in Enterococcus , Streptococcus , Corynebacterium and Gram-negative Pseudomonas species [Ojo et al, 2006].…”
Section: Msr(a)mentioning
confidence: 99%